APLIKASI PUPUK SI ORGANIK DENGAN PUPUK N,P,K DALAM MENINGKATKAN P DAN SI TANAH PADA INCEPTISOL JATINANAGOR TERHADAP RESPON TANAMAN HANJELI (Coix lacryma Jobi L.) - Eso Solihin; Anni Yuniarti; Apong Sandrawati; Zaenal Mutaqin (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2018)
The objective of this research was to determine the effect of combinations of N, P, K and organic silica fertilizers In Soil P and Si and growth Of Job’s Tears (Coix Lacryma Jobi L.). This research began on May 2017 to October 2017. This research has been done in experimental of Faculty Agricultural, Padjadjaran University Jatinangor. The experiment was in Randomized Block Design (RCBD) consisting of ten treatments with three replications; (A) Control, (B) NPK standard, (C) NPK + ¼ Silica Emulsion, (D) NPK + ½ Silica Emulsion, (E) NPK + ¾ Silica Emulsion, (F) NPK + 1 Emulsion of Ash Silica , (G) NPK + ¼ Nano Colloidal Silica, (H) NPK + ½ Nano Colloidal Silica, (I) NPK + ¾ Nano Colloidal Silica, (J) NPK + 1 Nano Colloidal Silica. The results showed that there was effect of Si fertilizer on soil P and plant growth. Treatment (J) NPK + 1 Colloidal Nano Silica gives Hanjeli the highest yield 5 MST, 7 MST, 9 MST and 11 MST with plant height 3.58 cm, 10.58 cm, 17.17 cm and 18.00 cm